Diplopia Following the Insertion of a Canalicular Bypass Tube: Etiology, Risk Factors, Management, and Outcomes. (May 2021) - Bladen, John C.; Mombaerts, Ilse; Kakizaki, Hirohiko; McNab, Alan A.; Norris, Jonathan H.; Verity, David; DeAngelis, Dan D.; Ataullah, Sajid M.; McCormick, Austin G.; Parkin, Ben; Patel, Bhupendra C. K.; Morley, Ana M. S.; et al.
Abstract : Purpose: To report the etiology, management, and possible risk factors for diplopia after canalicular bypass surgery. Methods: A multicenter retrospective, noncomparative case series of patients who developed diplopia following canalicular bypass surgery were assessed. Results: Twenty-four cases of diplopia were identified across 12 institutions. Tubes were inserted as a primary procedure with external dacryocystorhinostomy (DCR) (1; 4%) or without DCR (10; 42%) or as a secondary procedure after external (8; 33%) or endonasal (5; 21%) DCR. Factors predisposing to local damage were noted in 17 (71%): these factors included preexisting autoimmune/inflammatory condition (7 cases), medial canthal tumor resection (5 cases), preoperative radiotherapy (2 cases), 2 drug treatments (topical and systemic), and 1 local surgery. Horizontal diplopia was due to restriction of abduction and first noted at a median of 3.5 months (mean: 17.8 months, range: 1 day to 112 months) and persisted in 23 (96%) cases with a mean restriction of −2, affecting primary gaze in 4 patients and activities of daily living in 13 (42%). Seventeen patients received various treatments: 10 were operated on resulting in cure in 1 and improvement in 9. A stable degree of diplopia persisted in all but one patient. Conclusions: Restriction of abduction causing horizontal diplopia is a rare complication with canalicular bypass surgery and a notably high proportion occurred after tube placement without DCR; carunculectomy was not ubiquitous. Although in some the diplopia may be improved with intervention, the chance of cure is low. This complication should probably be included during informed consent for canalicular bypass tubes. Abstract : This study summarizes the possible etiology of diplopia after canalicular bypass surgery and reviews the various management options and subsequent outcomes.